1997
DOI: 10.1007/s004200050174
|View full text |Cite
|
Sign up to set email alerts
|

Biological monitoring of styrene exposure and possible interference of acetone co-exposure

Abstract: The object of this study is the evaluation of some of the toxicokinetic effects of exposure to low concentrations of styrene, and the possible influence of simultaneous exposure to acetone. To this end we studied 19 workmen simultaneously exposed to both solvents. During a week of 4-h work shifts, the workmen underwent daily personal environmental monitoring and the collection of urine samples, at both the beginning and the end of the work period, for the determination of mandelic acid (MA) and phenylglyoxylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 16 publications
2
10
1
Order By: Relevance
“…Our data also con®rm previous ®ndings (Sollenberg et al 1988;Imbriani et al 1990;Marhuenda et al 1997) of higher styrene metabolite levels towards the end of the workweek. Thus, information about the timing of sampling should be ascertained when evaluating dierences in metabolite levels from one time period to another or between dierent groups of workers, to ensure that valid comparisons are made.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our data also con®rm previous ®ndings (Sollenberg et al 1988;Imbriani et al 1990;Marhuenda et al 1997) of higher styrene metabolite levels towards the end of the workweek. Thus, information about the timing of sampling should be ascertained when evaluating dierences in metabolite levels from one time period to another or between dierent groups of workers, to ensure that valid comparisons are made.…”
Section: Discussionsupporting
confidence: 82%
“…Others, such as alcohol consumption (Wilson et al 1983;Berode et al 1986;Cerny et al 1990), co-exposure to other solvents (Marhuenda et al 1997;Apostoli et al 1998), and workload (Pezzagno et al 1988) may interfere with styrene metabolism or aect absorption. Unfortunately, data on these variables were not available, so it was not possible to evaluate their roles in explaining the variation in urinary metabolite levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field studies for effects on VOC metabolism after combined exposure mostly for aromatic hydrocarbons [107][108][109][110][111][112][113][114] are summarized in Table 10. Table 9 Experimental exposure of volunteers to solvent mixtures: effects on metabolism [98] (either the maximum non-effective dose or the minimum effective dose is given when two or more concentrations were tested).…”
Section: Influence Factors On Biomonitoring Results After Voc Exposurementioning
confidence: 99%
“…1993). However, Marhuenda et al (1997) showed that the urinary excretion of styrene metabolites (mandelic acid and phenylglyoxylic acid) during 4 hr work shifts was inversely correlated with the intensity of acetone exposure. Whether acetone during short-term exposure is able to interact with the metabolism of styrene therefore needs more research.…”
Section: Discussionmentioning
confidence: 99%